下顎骨に転移したと考えられる髄膜腫の1例 - 西尾, 佳朋; 風岡, 宜暁; 山本, 康博; 大野, 隆之; 古橋, 明文; 柘植, 祥弘 (日本口腔外科学会雑誌, 2019)
Most meningiomas are intracranial tumors arising from meningothelial cells. However, extracranial meningiomas can develop as a true primary extracranial meningioma or as a direct extension or distant metastasis from a primary intracranial meningioma. Extracranial meningiomas of the jaw are extremely rare. To the best of our knowledge, only nine cases of extracranial meningioma of the mandible have been reported to date. Here we report a case of extracranial meningioma of the mandible arising in an 83-year-old man who presented with a painless swelling in the left side of the mandible. Radiographic examination revealed a radiolucent lesion in the left side of the mandible, which was diagnosed as a meningothelial meningioma on biopsy. The patient previously underwent intracranial tumorectomy for a convexity meningioma and CyberKnife treatment for a residual tumor after surgery. Therefore, this lesion was considered mandibular bone metastasis from intracranial meningioma. Surgical therapy was proposed for treatment; however, consent was not obtained. After continued follow-up, no increase in the tumor was observed for 2 years after the first visit..